Letters of Chairmen of Urdu Encyclopaedia of Islam to Dr. Muhammad Hamidullah - Muhammad Arshad (بازیافت)
This article reproduces 28 unpublished letters of Prof. Maulavi Muhammad Shafi, the founder chairman of the editorial board of the Urdu Encyclopedia of Islam and his successors (Dr. Muhammad Wahid Mirza, Allama Alauddin Siddiqui, Prof. Hamid Ahmad Khan and Dr. Sayyid Abdullah), addressed to Dr. Muhammad Hamidullah (1908-2002). The project of compilation of Encyclopedia of Islam in Urdu was launched in 1950 by the University of the Punjab and Prof. Maulavi Muhammad Shafi (1883-1963), the former Principal of the Punjab University Oriental College(1936-1942), was appointed as the chairman of the editorial board. For the compilation of this Encyclopaedia, a foreign editorial board was constituted and Dr. Muhammad Hamidullah, residing in Paris, was appointed as honorary secretary. During the years 1951-1963, an intensive correspondence between Prof. Shafi and Dr. Muhammad  Hamidullah took place. During that period, Dr. Hamidullah made a remarkable contribution to this project. To seek scholarly contribution, Prof. Shafi's successors at the Department of Urdu Encyclopaedia of Islam also corresponded with Dr. Hamidullah, though its scale was gradually reduced.This collection of letters is quite interesting, as it sheds light on the daunting and tremendous task of the compilation of Urdu Encyclopedia of Islam  and the contribution of Dr. Muhammad Hamidullah, to this encyclopedia.